PGPR Kosakonia Radicincitans KR-17 Increases the Salt Tolerance of Radish by Regulating Ion-Homeostasis, Photosynthetic Molecules, Redox Potential, and Stressor Metabolites - Shahid, Mohammad; Al-Khattaf, Fatimah S.; Danish, Mohammad; Zeyad, Mohammad Tarique; Atef Hatamleh, Ashraf; Mohamed, Abdullah; Ali, Sajad (Frontiers in Plant Science, 2022)
Among abiotic stresses, salinity is a significant limiting factor affecting agricultural productivity, survival, and production, resulting in significant economic losses. Considering the salinity problem, the goal of this study was to identify a halotolerant beneficial soil bacterium to circumvent salinity-induced phytotoxicity. Here, strain KR-17 (having an irregular margin; a mucoid colony; Gm-ve short rod; optimum temperature, 30°C; pH 7.0; no any pigmentation; showed a positive response to citrate utilization, catalase, starch, sucrose, lactose, and dextrose, etc.) recovered from rhizosphere soils of the potato-cultivating field, tolerated surprisingly a high (18% NaCl; 3.-M concentration) level of salt and identified as Kosakonia radicincitans (Accession No. OM348535). This strain was discovered to be metabolically active, synthesized essential PGP bioactive molecules like indole-3-acetic acid (IAA), siderophore (iron-chelating compounds), ACC deaminase, and ammonia, the quantity of which, however, increased with increasing NaCl concentrations. Here, Raphanus sativus L. (radish) was taken as a model crop to evaluate the adverse impact of NaCl, as well as salinity alleviation by halotolerant K. radicincitans. Salinity-induced toxicity to R. sativus was increased in a dose-dependent way, as observed both in vitro and in vivo conditions. Maximum NaCl levels (15%) demonstrated more extreme harm and considerably reduced the plant's biological features. However, membrane damage, relative leaf water content (RLWC), stressor metabolites, and antioxidant enzymes were increased as NaCl concentration increased. In contrast, halotolerant K. radicincitans KR-17 relieved salinity stress and enhanced the overall performance of R. sativus (L.) by increasing germination efficiency, dry biomass, and leaf pigments even in salt-challenged conditions. Additionally, KR-17 inoculation significantly (p ≤ 0.05) improved plant mineral nutrients (Na, K, Ca, Mg, Zn, Fe, Cu, P, and N). Following inoculation, strain KR-17 enhanced the protein, carbohydrates, root pigments, amino acids (AsA and Lys), lipids, and root alkaloids in R. sativus (L.). Besides these, due to PGPR seed priming in NaCl-stressed/non-stressed conditions, membrane damage, RLWC, stressor metabolites, and antioxidant defense enzymes were dramatically reduced. The strong biofilm-forming capacity of K. radicincitans could result in both in vitro and in vivo colonization under NaCl stress. Conclusively, halotolerant K. radicincitans KR-17 may probably be investigated affordably as the greatest way to increase the production of radish under salinity-stressed soils.